Embarkations - paglalakbay trajectories of flight - Philippines Cultural Studies Center (Storrs, Conn. Philippines Cultural Studies Center, 2010)
Experimental video of multimedia rendering of poems, montages of scenes and landscapes, an other filmed happenings. Trajectories of flight from subaltern voyeur, Metro Manila visions and zen-scapes of the neocolonial and insurgent Philippine society of the spectacle.
Lunar eclipse - eklipse ng buwan [poem about Juan Luna] (9 min., 37 sec.) -- After May Day 2009, one day in Cambridge, Mass., [14th annual Harvard Pow Yow 2000, tour around community center (19 min., 40 sec.) -- Kalatas mula sa anghel = communication from the angel [poem declaring love and devotion] -- vision no. 1. Commonwealth Ave., Philcoa, Quaipo Nazareno parade (9 min., 52 sec.) -- Problema ng makata sa panahon ng terorismo [poem] (8 min., 32 sec.) -- Balikbayang sinta [8 min., 51 sec.] -- visions no. 7. Makati Gloria Resign rally (9 min., 57 sec.) -- zen-scape no. 12. montage (10 min., 36 sec.) -- Joiussance = libog [poem] (15 min., 12 sec.) -- subaltern voyeur no. 7. epilogue (9 min., 59 sec.)
Summary from container.
DVD.
Keywords: San Juan, Epifanio, Jr. -- Poetry; Luna, Juan Novicio -- 1857-1899.; Philippines -- Social conditions; Visual anthropology